LEARNING CIRCULAR ECONOMY IN HIGHER EDUCATION: A PEDAGOGICAL MODEL FOCUSED ON SOCIAL IMPACT - Morejón, Víctor Manuel Molina; de la Peña, Horacio Monsiváis; Mendoza, Vanessa Espitia; Gurrola, Eyran Roberto Díaz; Arellano, José de Jesús Espinoza (Seven Editora, 2026)
The circular economy (CE) is a key alternative in the face of current environmental and production-related challenges. Its teaching requires pedagogical approaches that integrate theory, practice, and critical reflection. In this study, a course was designed that not only delivered theoretical content, but also strengthened students’ ability to apply the CE as a framework for innovation, sustainability, and responsible decision-making. This university course was based on constructive alignment and participatory action research; it included lectures, guided discussions, collaborative work, and practical activities. The methodology was grounded in constructive alignment, ensuring that each activity and assessment corresponded to the established learning objectives. In addition, the methodology incorporated the use of PLS-SEM, a technique suitable for analyzing complex models based on perceptions through latent constructs derived from the empirical data collected, which made it possible to rigorously evaluate the relationships among the model’s variables and provide statistical evidence of their consistency. The authors observed that the course enabled students to connect the principles of social entrepreneurship with solutions to real-world problems, while also highlighting the relevance of social and educational variables as driving factors for integrating CE into higher education. Furthermore, education for social entrepreneurship is supported by learning theories and adaptive technologies that facilitate personalized learning experiences. The findings of this investigation align with these methodologies, since they reside within statistically acceptable parameters, hence reinforcing the validity of the suggested model.